Cerebral function parameters in people with HIV switching integrase inhibitors: a randomized controlled trial. Issue 6 (15th December 2021) - Mora-Peris, Borja; Keegan, Michael R.; Penchala, Sujan Dilly; Vera, Jaime H.; Underwood, Jonathan; Khan, Maryam; Herrera, Carolina; Fuchs, Dietmar; Boasso, Adriano; Khoo, Saye; Winston, Alan
Abstract : Background: Different antiretroviral therapies (ARTs) may have differing effects on central nervous system (CNS) function. We assessed CNS pharmacodynamic effects of switching integrase inhibitors in people-with-HIV (PWH). Methods: PWH on tenofovir-DF/emtricitabine plus raltegravir 400 mg twice daily with suppressed plasma HIV RNA and without overt neuropsychiatric symptoms were randomly allocated on a 1:2 basis to remain on raltegravir or switch to dolutegravir 50 mg once daily for 120 days. Pharmacodynamic parameters assessed included cognitive function ( z -score of 7 domains), patient-reported outcome measures (PROMs; PHQ-9 and Beck's depression questionnaires), cerebral metabolite ratios measured by proton magnetic resonance spectroscopy (H 1 -MRS) and plasma and cerebrospinal fluid (CSF) HIV RNA. Pharmacokinetic parameters were also assessed in plasma and CSF. Changes and factors associated with changes in pharmacodynamics parameters were assessed. Results: In 20 subjects (19 male, 14 white ethnicity, median age 43 years (IQR: 11.5) and CD4 + count 717 (SD: 298) cells/µL), over 120 days there were no statistically significant changes in cognitive function [mean z -score difference (95%CI) −0.004 (−0.38/0.37); p = 0.98], PROMs [PHQ-9 median score change: 0 in control arm, −0.5 switch arm ( p = 0.57); Beck's depression questionnaire: −1.5 control arm, −1.0 switch arm ( p = 0.38)], nor cerebral metabolite ratios between study arms. CSF HIV RNA was <5 copies/mL at baseline and day 120 in all subjects. Geometric mean pre-dose CSF dolutegravir concentration was 7.6 ng/mL (95% CI: 5.2–11.1). Conclusions: Switching integrase inhibitor in virologically suppressed PWH without overt neuropsychiatric symptoms resulted in no significant changes in an extensive panel of CNS pharmacodynamics parameters.